Persepsi Pengunjung Terhadap Produk Wine Lokal Sababay Winery Sebagai Wisata Gastronomi Di Bali - Joanne, Marie Josephine; Nugroho, Saptono (JURNAL DESTINASI PARIWISATA, 2023)
Sababay Winery is a company that produces, processes, and introduces local Balinese wine products through gastronomy and wine tourism in Bali which is currently popular with foreign and domestic visitors. The purpose of this research is to analyze the perceptions of domestic visitors towards the local wine products of Sababay Winery as a form of gastronomy tourism in Bali. The research method used is a mix methods concurrent embedded approach which is predominantly qualitative with qualitative and quantitative data. Methods of collecting primary and secondary data in this study through questionnaires, interviews, observation, and documentation. The sampling technique is non-probability sampling with a total sample of 75 respondents. The technique of determining informants used a purposive sampling technique with consideration of the position of the informant in the company, with a total of two informants from the company Sababay Winery. Based on the results of the questionnaire using the Likert scale showed the perceptions of domestic visitors towards the local wine products of Sababay Winery on three aspects, namely, cognitive aspects (price, packaging, marketing, promotion, and competitiveness), affective aspects (taste, aroma, texture, body, aftertaste, and compatibility of food and wine pairing), and conative aspects (level of desire to buy and rebuying Sababay wine products, as well as motivation to buy Sababay Winery Tour tour packages) in this study on average showed positive results of domestic visitors' perceptions of Sababay local wine products, with the lowest score of 4,07 from a score of 5, to the highest score of 4,32 out of a score of 5, which is still in the Agree to Strongly Agree category. Keywords: Sababay local wine products, wine tourism, gastronomy tourism, domestic visitor perceptions